Counterion‐Switched Reversibly Hydrophilic and Hydrophobic TiO2‐Incorporated Layer‐By‐Layer Self‐Assembled Membrane for Nanofiltration. Issue 12 (9th October 2019) - Guo, Hongxia; Yu, Shaocheng; Liu, Tongtong; An, Quan‐Fu; Ren, Xiaoyan; Qin, Zhenping; Liang, Yucang
Abstract: The manipulation of surface wettability has been regarded as an efficient strategy to improve the membrane performances. Herein, the counterion‐switched reversibly hydrophilic and hydrophobic surface of TiO2 ‐loaded polyelectrolyte membrane are prepared by layer‐by‐layer assembly of poly(sodium 4‐styrene sulfonate) (PSS) and poly(diallydimethyl‐ammoniumchloride (PDDA) containing TiO2 @PDDA nanoparticles (NPs) on the hydrolyzed polyacrylonitrile (PAN) substrate membrane. The obtained polyelectrolyte multilayer (PEM) membranes [PEM‐TiO2 ]4.5 + X − (X − = Cl −, PFO − [perfluorooctanoate] etc.) show different hydrophilicity and hydrophobicity with various counterions. The integration of TiO2 NPs obviously improves the wettability and nanofiltration (NF) performance of PEM membrane for (non)aqueous system of dyes (crystal violet, eriochrome black T) with a high recyclability. The highly hydrophilic [PEM‐TiO2 ]4.5 + Cl − (water contact angle [WCA]: 13.2 ± 1.8°) and hydrophobic [PEM‐TiO2 ]4.5 + PFO − (WCA: 115.4 ± 2.3°) can be reversibly switched via counterion exchange between Cl − and PFO −, verifying the surface with a reversible hydrophilic–hydrophobic transformation. For such membranes, the morphology, wettability, and NF performance rely on the loading of TiO2 @PDDA NPs and surface counterion. Meanwhile, the motion and interaction of water or ethanol in the hydrophilic or hydrophobic membrane are revealed by low‐field nuclear magnetic resonance. This work provides a facile and rapid approach to fabricate smart and tunable wetting surface for potential utilization in (non)aqueous NF separation. Abstract : Counterion‐switched reversibly hydrophilic and hydrophobic TiO2 ‐incorporated polyelectrolyte composite membranes on PAN substrate are prepared by LbL assembly of TiO2 ‐incorporated PDDA and PSS and posttreated ion‐exchange process. Hydrophilicity and hydrophobicity can be reversibly switched via counterion exchange. All optimal nanocomposite membranes show an enhanced nanofiltration performance in aqueous and ethanol solution of dyes as well high stability and reusability.